2003
DOI: 10.1080/0968763031000082124
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Distilled Spirits Consumption and Violent Mortality Rate

Abstract: The association between alcohol and violent mortality is well documented.Considerably less is known about the beverage-specific effect of alcohol on mortality rate. The role of drinking patterns in the alcohol-violent mortality association is a very important issue today. Aim: To estimate the beverage-specific effect of alcohol on violent mortality rate. Measurement: Trends in different types of violent mortality rate (mortality due to accidents and injuries, mortality due to suicide and homicide, mortality du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
31
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 33 publications
7
31
1
1
Order By: Relevance
“…There is a growing literature on the detrimental effects of stress on Russians during the transition Shkolnikov and Meslé 1996), including higher levels of drinking in the early 1990s. More generally, even without this increase, the Russian level of alcohol consumption is among the highest in the world (Bobak et al 1999;Nemtsov 2000), and alcohol has been found to be associated with homicide in Russia and Eastern Europe in a growing number of studies (Andrienko 2001;Pridemore 2004;2002a;Razvodovsky 2003). Nevertheless, the findings presented here show a significant drop in the proportion of those convicted of homicide who were drinking at the time of the event.…”
Section: Discussioncontrasting
confidence: 54%
“…There is a growing literature on the detrimental effects of stress on Russians during the transition Shkolnikov and Meslé 1996), including higher levels of drinking in the early 1990s. More generally, even without this increase, the Russian level of alcohol consumption is among the highest in the world (Bobak et al 1999;Nemtsov 2000), and alcohol has been found to be associated with homicide in Russia and Eastern Europe in a growing number of studies (Andrienko 2001;Pridemore 2004;2002a;Razvodovsky 2003). Nevertheless, the findings presented here show a significant drop in the proportion of those convicted of homicide who were drinking at the time of the event.…”
Section: Discussioncontrasting
confidence: 54%
“…Recent findings led some scholars to assert that wet drinking cultures may be less susceptible to an association between alcohol and suicide than dry cultures (Norström 1995a, Ramstedt 2001. In contrast, the results from some studies lead others to argue that it may not be simply the level of consumption but instead heavy and frequent binge drinking (commonly defined in the alcohol literature as five drinks NIH Public Access for men and four for women in one sitting), especially of distilled spirits (e.g., vodka, rum, whiskey and gin), that is most important in any association with suicide rates (Gruenewald, Ponicki and Mitchell 1995;Razvodovsky 2003;Rossow 2000). Both hypotheses are important for Russia given levels of binge drinking (Bobak et al 1999) and the preference for distilled spirits (Nemtsov 2000).…”
mentioning
confidence: 86%
“…In relation to this, it should be emphasized, that the fatal alcohol poisonings and traffic accidents mortality trends have been more or less correlated with the great societal transformation [19]. One of the most intriguing phenomenon in this context is the substantial decline in alcohol consumption and traffic mortality rates that occurred between 1980 and 1984, which might be attributed to the increase in the price of vodka in 1981 [7]. Furthermore, the new Soviet leader Andropov, who came to power in 1982, realized that mass drunkenness was a major threat to the Soviet system and saw a great opportunity to increase labor productivity by sobering up the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Among females the effect was significant only in central Europe [6]. A more recent time series analysis based on Belarusian data for the period from 1970 to 1999 reported a close link between vodka sales per capita and road traffic fatality rates [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation